Field Trip Report: Loita exchange visit and training at Drylands Natural Resources Centre (DNRC), Makueni - Bedelian, Claire; Notenbaert, An Maria Omer (International Livestock Research Institute, 2024)
A group of 20 Maasai livestock farmers from Loita in Narok County travelled to the DNRC in Makueni County for a two-day exchange visit and training. DNRC is a training centre specialising in drylands agriculture, agroecology, permaculture and agroforestry. The centre supports 900 farmers in implementing sustainable practices on their farms and hosts exchange visits for visiting groups. It also incorporates training on Kamba culture, including traditional food, music, and crafting techniques for items such as stools and beehives. The 20 participants came from different areas of Loita, including both the forested and plains areas. The group comprised of farmers actively engaged in crop farming as well as those interested in learning new approaches to their crop and livestock production. Having recently been allocated parcels of land ranging from 8 to 15 acres, they were keen to explore sustainable practices beyond extensive livestock production, which is becoming increasingly limited due to land privatisation. Those with plots in the mature forest areas were particularly interested in understanding tree-crop-livestock interactions and strategies to manage their land for the benefit of their livelihoods, their livestock and crops, and the environment. Among the group were several couples who jointly owned newly allocated adjacent parcels of land, as married women were equal recipients of land in Loita. Participants were eager to learn from innovative dryland farming practices and identify practical solutions they could implement in their community.